Ação dos alcalóides totais da Schultesia guyanensis malme na musculatura lisa do canal deferente isolado de rato - Lima, Maria Edlene Felix de (1996)
Schultesia guyanensis Malme (Schultesia stenophilla Mart., Exacum guianensis Aubl.) is a herb that belongs to the family, Gentianaceae. It is popularly known as “mata-zombando”, since it is believed to be deadly toxic to cattle. The present study utilized Schultesia guyanensis total alkaloids (SgTA) and studied their pharmacological activity on isolated rat vas deferens. Isotonic and isometric contractile responses to agonists were registered in the absence and presence of SgTA and the data were collected through analysis of concentration-response curves (CRC). Initially, we tested three different concentratios of SgTA ( 35, 75 and 100 Lig/ml), on contractile responses evoked by noradrenaline. We observed a steep increase in the CRC, without any significant change in the CE50 (effective concentration for 50% maximal response) value. The increase in maximal response was found to be proportional to the concentration of SgTA used. The increases were in the order of 8, 22 and 37% for the respective concentration of 35, 75 and 100 pg/ml. Based on this, a concentration of 100 pg/ml was chosen for the subsequent studies.